Scaling Up of the Pyrolysis Process to Produce Silica from Rice Husk - Casnan Casnan; Erliza Noor; Hartrisari Hadjomidjojo; Irzaman Irzaman; Eti Rohaeti (Journal of Engineering and Technological Sciences, 2019)
Rice husk is a potential alternative source of silica and silicon. The mechanism of heating (pyrolysis) for the decomposition of rice husk is an important factor in obtaining silica of high purity. Medium-scale pyrolysis to produce silica from rice husk serves as a bridge to connect laboratory-scale production to industrial-scale production. The purpose of this study was to model and scale up the pyrolysis process as a guidance for industrial-scale production. The research method used was experimentally based. An experimental investigation was undertaken in five stages. 1) Analyzing rice husk mass conversion using thermogravimetry analysis (TGA); 2) pyrolysis modeling based on a laboratory investigation using COMSOL Multiphysics version 5.3; 3) medium-scale experiments according to the modeling results; 4) validation of the modeling results by carrying out a medium-scale experiment; 5) silica purity analysis using SEM-EDX. The medium-scale pyrolysis simulation of silica manufacture from rice husk obtained a heating rate of 1.5 °C/min. There was an increase in the heating rate of 1 °C/min when compared to the laboratory-scale process. The pyrolysis of rice husk for the production of silica affects the mass conversion and selectivity of the resulting silica product. The mass conversion produced was 13.33% to 17.87% and the purity of silica produced was 63.99% to 82.74%.